1995
DOI: 10.1128/jb.177.20.5918-5923.1995
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characterization of 4-amino 4-deoxychorismate synthase from Escherichia coli

Abstract: The metabolic fate of p-aminobenzoic acid (PABA) in Escherichia coli is its incorporation into the vitamin folic acid. PABA is derived from the aromatic branch point precursor chorismate in two steps. Aminodeoxychorismate (ADC) synthase converts chorismate and glutamine to ADC and glutamate and is composed of two subunits, PabA and PabB. ADC lyase removes pyruvate from ADC, aromatizes the ring, and generates PABA. While there is much interest in the mechanism of chorismate aminations, there has been little wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 21 publications
(20 reference statements)
2
40
0
Order By: Relevance
“…ABZ2 ENCODES YEAST AMINODEOXYCHORISMATE LYASE 2109 on May 13, 2018 by guest http://ec.asm.org/ dimers and inactive monomers could be the basis of a mechanism of activity regulation of this enzyme, which does not appear to be feedback regulated for PABA or folates (5,42), and neither does its expression seem to be subject to transcriptional control (our unpublished results). Although unlikely, the possibility still exists that the presence of Abz2p monomers in the enzyme preparation could be an artifact due to the presence of an N-terminal His 6 tag in the recombinant protein used in our analyses.…”
Section: Vol 6 2007mentioning
confidence: 99%
“…ABZ2 ENCODES YEAST AMINODEOXYCHORISMATE LYASE 2109 on May 13, 2018 by guest http://ec.asm.org/ dimers and inactive monomers could be the basis of a mechanism of activity regulation of this enzyme, which does not appear to be feedback regulated for PABA or folates (5,42), and neither does its expression seem to be subject to transcriptional control (our unpublished results). Although unlikely, the possibility still exists that the presence of Abz2p monomers in the enzyme preparation could be an artifact due to the presence of an N-terminal His 6 tag in the recombinant protein used in our analyses.…”
Section: Vol 6 2007mentioning
confidence: 99%
“…1). In the first step, the PabA and PabB proteins cooperate to replace the hydroxyl group of chorismate with an amino group, yielding 4-amino-4-deoxychorismate (ADC) (4,9). PabA acts as a glutamine amidotransferase, supplying an amino group to PabB, which carries out the amination reaction.…”
mentioning
confidence: 99%
“…Secondly, PABA synthases contain an extra region between the PabA and PabB domains that could potentially carry a novel ADC lyase activity. Lastly, PabA and PabB are, respectively, homologous to TrpG and TrpE, which convert chorismate all of the way to the PABA analog anthranilate (o-aminobenzoate) without need of a lyase (9,15). It thus remains to be established whether PABA synthases are bifunctional (i.e., strictly equivalent to PabA and PabB) or trifunctional, having in addition ADC lyase activity.…”
mentioning
confidence: 99%
“…[10] Two of these strains (ΔpabA and ΔpabB) have mutations in the genes encoding the two subunits of aminodeoxychorismate synthase, which catalyzes the penultimate step in PABA biosynthesis. [11] The third mutant (ΔaroC) is missing the gene encoding key shikimate pathway enzyme chorismate synthase, and is unable to synthesize not only PABA but also the aromatic amino acids L-phenylalanine, L-tyrosine, and L-tryptophan, as well as the aromatic metabolites para-hydroxybenzoic acid (PHBA) and 2,3-hydroxybenzoic acid. [12] We confirmed that all three strains were unable to grow in PABA-free M9 glycerol minimal media and established each strain's inability to utilize substrate 1 in place of PABA.…”
Section: Author Manuscriptmentioning
confidence: 99%